THE ROLE OF ABDURAUF FITRAT’S THOUGHTS ABOUT HUMANITY AND TOLERANCE IN FAMILY ETHICS IN EDUCATION OF YOUTH - Ism?il Saifnazarov; Tursunboy Sultonov; Rohatoy Khalimmetova; Dilmurod Ernazarov; Azizjon Mamirov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this article, the role of the views of Abdurauf Fitrat, who is one of the great representatives of the Turkestan Jadid movement in the early twentieth century, about humanity and tolerance on family ethics, in the education of young people is described. It is scientifically interpreted that Fitrat in his works delves deeply into the need for marriage, the tolerant relationship of family members, the rights and duties of parents, children, and even the upbringing of infants and how young mothers should behave in it. Therefore, this scientific article emphasizes the role of tolerance as a social factor in the family and society, with special attention to the socio-ethical and labor education of children. It is also analyzed that a healthy, enlightened family and a comprehensively mature generation, which he brings up, are important conditions for the foundation of the country’s glory and power